"NÓS SOMOS MUITO MAIS": Cartografando por entre espaços, nomes, corpos em busca de concepções transviadas de saúde - Daniella Chagas Mesquita (2021)
This research, from a qualitative approach and an unpretentious listening, proposes a cartography and analysis of conceptions and senses of health experienced by travestis and trans women. These senses, cartographyed in events, dialogues and interviews allocated in Campo Grande-MS (Brazil), were analyzed firstly from contrasts, tensioning and negotiations with hegemonic models of health, especially the biomedical model, that tend to reduce its discussions about trans population health in topics of prevention and treatment of sexually transmitted infections or in the transsexualizing process, and as an effect, other issues, also important in their day-to-day, were misplaced. I understand that these counterhegemonic experiences and understandings by travestis and transexual people point to an expanded conception of health, which I denominate transviada health. These analytical category points to the limits of a health concept delimited by biomedical norms and to the possibility of one incarnate, affective and militant conception of health, which is built through the memory of travestis and transexuals.